(untitled) (Sciences & Technologie. C, Biotechnologies, 2011)
Studies of gastric biopsies taken from ten hospitalised patients suffering from gastroduodenal diseases and were subjected to a oesogastroduodenal fibroscopy, with a fast urease test, histological, cytological examination and a microbiological culture make the evidence of H.pylori. We had isolated H.pylorifrom seven patients among the ten patients having an infection with H.pyloriannounced by histology and urease test. H.pyloriidentification was based on the morphological and biochemical characters. Our research was reinforced by the realization of an antibiogram which can guide us towards an antibiotherapy for the eradication of H.pyloriinfection.